1998
DOI: 10.1093/carcin/19.6.1127
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional effects and DNA-binding specificities of 17beta- estradiol after dimethyldioxirane activation

Abstract: It was found recently that 17β-estradiol (E2) could be activated by the epoxide-forming oxidant dimethyldioxirane (DMDO) resulting in the inhibition of rat liver nuclear and nucleolar RNA synthesis in vitro (Carcinogenesis, 17, 1957(Carcinogenesis, 17, -1961(Carcinogenesis, 17, , 1996. To further study the mechanism of this inhibition, several synthetic DNAs with different base content and sequence were used to study the transcriptional effects and binding specificities of E2 after DMDO activation in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Therefore, one of the important tests of our hypothesis is to determine whether E 1 and E 2 after DMDO activation are able to bind to DNA. In support to our hypothesis, we have found that 3 H‐labelled E 1 and E 2 are able to bind to both G‐C and A‐T containing DNAs but only after DMDO activation [10,11]. Additionally, the covalent binding nature of E 1 and E 2 to DNA after DMDO activation was further confirmed by 32 P‐post‐labelling analysis using calf thymus as well as several synthetic DNAs of a known base content and sequence [10,11].…”
Section: Introductionsupporting
confidence: 83%
“…Therefore, one of the important tests of our hypothesis is to determine whether E 1 and E 2 after DMDO activation are able to bind to DNA. In support to our hypothesis, we have found that 3 H‐labelled E 1 and E 2 are able to bind to both G‐C and A‐T containing DNAs but only after DMDO activation [10,11]. Additionally, the covalent binding nature of E 1 and E 2 to DNA after DMDO activation was further confirmed by 32 P‐post‐labelling analysis using calf thymus as well as several synthetic DNAs of a known base content and sequence [10,11].…”
Section: Introductionsupporting
confidence: 83%
“…3). 24,25 The covalent binding nature of E 1 and E 2 to DNA was further confirmed by [ 32 P]‐post‐labelling analysis (Fig. 4).…”
Section: β‐Estradiol Epoxidation As the Underlying Mechanism Of Brementioning
confidence: 71%
“…It is clear that in order to properly prevent a disease, it is necessary to know the cause of the disease. In terms of breast cancer, our findings that E 2 could be activated by epoxidation 13 and was consequently able to bind DNA, forming DNA adducts, in vitro and in vivo 24−26,28−30 have provided a strong molecular basis for an initiatory role of E 2 in breast cancer aetiology 13 . Based on this new insight, we have developed a technique to screen potential chemo­preventive agents at the initiation step of breast cancer carcinogenesis.…”
Section: β‐Estradiol Epoxidation As a Molecular Basis For Breast Camentioning
confidence: 92%
See 2 more Smart Citations